Social Construction Fandom as Cultural Industry Marketing of JKT 48 Fan Group - Mulyana, Ahmad; Briandana, Rizki; Ningrum, Dwi Anggraini Puspa (International Research Journal of Business Studies, 2019)
The aim of this research is to analyzed the social construction of marketing of the JKT48 fandom group in the context of the cultural industry context. The culture industry can be interpreted as cultural production and consumption or contribution to cultural production. This reality is one of the popular culture products which is quite popular with a group of JKT 48 fans. This study uses a case study method with interview and observation as data collection technique. The results show that the social construction of fandom is formed on the same interest in a cultural form. The presence of JKT48 gives a new color in forming a subculture about the concept of become a fan as a consumer of popular culture. This relates to the marketing of a culture as a form of cultural industry as a contribution in cultural production.